PERLINDUNGAN HUKUM BAGI NASABAH PADA LEMBAGA PERBANKAN - Ayu Suci Arini, Ni Nyoman; A. Martana, Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
Banking institution is an institution that is depentdent upon the trust of the public, without the trust of public, of a bank will not be able to run its businessproperly. Banking institution must maintain the trust of the public by providing legal protection of the public interests especially the interests of customers of the bank concerned. Therefore, this paper will describe the “Legal Protection For Depositors Funds In Banking Institition”. The paper also describes the necessity guarantees legal protection for depositors in the banking institution.
Keywords: Banking, Depositors, Funds, Institution